PELATIHAN PEMBUATAN PAKAN PASTA UNTUK MENGURANGI KEBUTUHAN PAKAN KOMERSIL PEMBUDIDAYA IKAN DI POKDAKAN MINA WEDANA DESA GLINGGANGAN PRINGKUKU PACITAN - Muhamad Amin; Rozi Rozi; Dita Wisduyawati; Shofy Mubaraq; Yudi Cahyoko; Shifania Hanifa Samara (Universitas Mataram, 2025)
The high price of commercial feed is one of the obstacles faced by many fish farmers. One solution that can be done is that fish farming communities need to be equipped with knowledge and skills on how to make alternative feeds such as pasta feed to reduce the use of commercial feed. The advantages of pasta feed are the nutritional value and relatively high level of digestibility, the manufacturing process is easy and requires simple equipment. Therefore, the community service team from the Faculty of Fisheries and Maritime Affairs at Airlangga University conducted training activities on pasta feed for catfish with partners from the Pacitan District Fisheries and Maritime Service and target partners from the Mina Wedana Fish Farmers Group (Pokdakan) in Glingnggang Pringkuku Pacitan Village. Through these activities it is hoped that cultivator groups will be able to provide feed independently so that they can reduce production costs, especially feed and increase profits.